Water-Assisted Synthesis of Molybdenum Disulfide Film with Single Organic Liquid Precursor - Choi, Soo Ho; Stephen, Boandoh; Park, Ji-Hoon; Lee, Joo Song; Kim, Soo Min; Yang, Woochul; Kim, Ki Kang (Nature Publishing Group, 2017)
We report on the synthesis of large-area molybdenum disulfide (MoS2) film on an insulating substrate by means of chemical vapor deposition. A single mixture of molybdenum hexacarbonyl (Mo(CO)(6)) and dimethyl disulfide (C2H6S2) was utilized as an organic liquid precursor for the synthesis of MoS2 film. Carbon impurities stemming from the dissociation of the organic precursor are effectively removed by water oxidation, and hydrogen gas, which is a by-product of the oxidation of carbon impurities, inhibits the formation of molybdenum oxides. The use of a liquid precursor assisted with water oxidation ensures high reproducibility and full-coverage of MoS2 film for large area, which is not typically achieved with solid precursors such as molybdenum oxide and sulfur powder. We believe that our approach will advance the synthesis of transition metal dichalcogenides.